2009
DOI: 10.1007/s10237-009-0148-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a mechano-regulation theory of skeletal tissue differentiation in an in vivo model of mechanically induced cartilage formation

Abstract: Mechanical cues are known to regulate tissue differentiation during skeletal healing. Quantitative characterization of this mechano-regulatory effect has great therapeutic potential. This study tested an existing theory that shear strain and interstitial fluid flow govern skeletal tissue differentiation by applying this theory to a scenario in which a bending motion applied to a healing transverse osteotomy results in cartilage, rather than bone, formation. A 3-D finite element mesh was created from micro-comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 29 publications
3
37
0
Order By: Relevance
“…The model predictions of tissue differentiation for the non-union of a fracture subject to cyclic bending loads can be compared to histological data from developing neoarthroses (Cullinane et al, 2002). The mechanoregulation algorithm predicted a mixture of cartilaginous and fibrous tissue, generally consistent with experimental findings and previous computational models (Cullinane et al, 2002(Cullinane et al, , 2003Hayward and Morgan, 2009). However we did not predict the bony arcade structures reported by Cullinane et al (2002).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The model predictions of tissue differentiation for the non-union of a fracture subject to cyclic bending loads can be compared to histological data from developing neoarthroses (Cullinane et al, 2002). The mechanoregulation algorithm predicted a mixture of cartilaginous and fibrous tissue, generally consistent with experimental findings and previous computational models (Cullinane et al, 2002(Cullinane et al, , 2003Hayward and Morgan, 2009). However we did not predict the bony arcade structures reported by Cullinane et al (2002).…”
Section: Discussionsupporting
confidence: 72%
“…These neoarthroses exhibited preferred fibre angles consistent with those seen in articular cartilage. Hayward and Morgan (2009) further demonstrated that the patterns of tissue differentiation observed experimentally could be predicted using the mechano-regulation theory of Prendergast et al (1997), providing further evidence to suggest that both strain and fluid flow are key regulators of tissue differentiation. What remains to be elucidated is the exact relationship between the mechanical environment and the molecular organisation of extracellular matrix at the repair site during skeletal tissue differentiation.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…For example, Ng. et al [14] found that collagen aligned perpendicular to subtle flow, Vera et al [15] found that fluid flow would constitute a beneficial environment for endothelial cells' reproduction, Hayward et al [16] found that interstitial fluid velocity and tissue shear stress are key mechanical stimuli for the differentiation of skeletal tissues. Until recently, the distribution of capillaries in humans was assumed to be a uniform network which has no orientation and no specificity.…”
Section: Introductionmentioning
confidence: 99%
“…By characterising the skeletal tissues as biphasic materials, Prendergast et al [7] proposed that a biophysical stimulus (a combination of fluid flow and shear strain) regulated tissue formation. Although the mechanoregulation theories of Carter et al [5], Claes and Heigele [6], and Prendergast et al [7] have been able to capture the main aspects of tissue differentiation, the predictions by the theory of Prendergast et al [7] have been most successfully correlated with experimental results [8][9][10][11]. Another key factor that regulates tissue differentiation is the formation of blood vessels.…”
Section: Introductionmentioning
confidence: 99%